Bahasa Inggris - Permana, Dwinda Abi; Shandy, Dwi Kunia (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2026)
The development of biomotor components, particularly speed and endurance, plays a crucial role in optimizing athletic performance during adolescence. This study aimed to examine the levels of speed and endurance among female adolescent athletes in the athletics discipline in East Java. A quantitative descriptive research design was employed to provide an empirical overview of these biomotor capacities. The participants consisted of 18 female athletes aged 15–16 years selected from the East Java athletics training program. Speed performance was assessed using a 30-meter sprint test, while endurance capacity was measured through the multistage fitness test to estimate maximal oxygen uptake (VO₂max). The findings revealed that the athletes demonstrated a very good level of speed with an average sprint time of 4.43 seconds, whereas endurance performance was categorized as good, with a mean estimated VO₂max of 36.58 ml/kg/min. These results indicate that although sprint capacity among the athletes is highly developed, endurance capacity remains relatively moderate and may require further training optimization. The findings provide important empirical insights for coaches and sport scientists in designing evidence-based training programs aimed at balancing the development of biomotor components in adolescent athletes